Circulating levels of matrix metalloproteinase-9 and abdominal aortic pathology: From the Dallas Heart Study - Grodin, Justin L (2011)
Prior reports have associated increased circulating levels of matrix metalloproteinase-9 (MMP-9), an endopeptidase active in the extracellular matrix, with the formation and rupture of aortic aneurysms, raising the possibility that MMP-9 may be a useful diagnostic or therapeutic target for aortic pathology. However, associations between MMP-9 and pathological abdominal aortic phenotypes in the general population have not been reported. In the Dallas Heart Study, a population-based sample of Dallas County residents (n = 2304), we measured MMP-9 and performed magnetic resonance imaging (MRI) of the abdominal aorta, measuring aortic compliance, plaque, wall thickness and luminal diameter. After adjustment for traditional cardiac risk factors and body size, higher MMP-9 quartiles were independently associated with higher aortic wall thickness and larger luminal diameter (p < 0.0001 for each), but not abdominal aortic plaque (p = 0.08), coronary artery calcium (p = 0.20) or the aortic luminal diameter/aortic wall thickness ratio (p = 0.37), supporting the hypothesis that therapies targeting MMP-9 may affect the abdominal aortic wall and modify aortic pathology.